Integration of Environmental, Social, and Governance (ESG) Factors into Target Costing in Lean Production Systems: A Systematic Literature Review - Ralfsamy, Achmad Daffa; Ruwary, Cinda Nongfasya; Alfarizi, Ikhsan; Ramadhan, M. Faalih Athoullah; Yusnaini, Yusnaini (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This systematic literature review critically challenges the reductionist paradigm of traditional Lean Production, arguing that its narrow focus on physical waste elimination often termed